Could someone please show me where I went wrong on this: 2x^2+2x-12=0 2x^2 +6x-4x-12=0 x(2x+6)(-4x-12)=0 2x+6=0,2x=-6, 2x/2=-6/2,x=-3 -4x=12,-4x/4=12/4 x=3
Last edited by wolfhound; Oct 6th 2009 at 05:17 AM. Reason: messy
Follow Math Help Forum on Facebook and Google+
Originally Posted by wolfhound Could someone please show me where I went wrong on this: 2x^2+2x-12=0 2x^2 +6x-4x-12=0 x(2x+6)(-4x-12)=0 <<<<<<<<< here 2x+6=0,2x=-6, 2x/2=-6/2,x=-3 -4x=12,-4x/4=12/4 x=3 I take this line: $\displaystyle 2x^2 +6x-4x-12=0~\implies~2x(x+3)-4(x+3)=0~\implies~(x+3)(2x-4)=0$ I'll leave the rest for you
Originally Posted by earboth I take this line: $\displaystyle 2x^2 +6x-4x-12=0~\implies~2x(x+3)-4(x+3)=0~\implies~(x+3)(2x-4)=0$ I'll leave the rest for you x=-3 and x=2 Thanks
View Tag Cloud